2009
DOI: 10.1158/1078-0432.ccr-08-1857
|View full text |Cite
|
Sign up to set email alerts
|

Src Family Kinase Activity Is Up-Regulated in Hormone-Refractory Prostate Cancer

Abstract: Purpose: Although Src family kinase (SFK) inhibitors are now in clinical trials for the treatment of androgen-independent prostate cancer (AIPC), there are no studies relating SFK activation to patient survival. This study was designed to determine if SFK activation was up-regulated with the development of AIPC and if patients could be selected who were more likely to respond to therapy. Experimental Design: A unique cohort of matched prostate tumor samples, taken before hormone deprivation therapy and followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
130
2
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(141 citation statements)
references
References 26 publications
(36 reference statements)
8
130
2
1
Order By: Relevance
“…This relationship results in robust activation of SRC tyrosine kinase and MAPK signaling (18). SRC activity was also observed in a subset of castration-resistant prostate cancer (CRPC) patients, which correlated with lower overall survival and increased metastatic disease (19). These data support the idea that tyrosine kinase activity may play a prominent role in prostate cancer progression in the absence of activating mutations.…”
mentioning
confidence: 53%
“…This relationship results in robust activation of SRC tyrosine kinase and MAPK signaling (18). SRC activity was also observed in a subset of castration-resistant prostate cancer (CRPC) patients, which correlated with lower overall survival and increased metastatic disease (19). These data support the idea that tyrosine kinase activity may play a prominent role in prostate cancer progression in the absence of activating mutations.…”
mentioning
confidence: 53%
“…Furthermore, SRC is involved in the signal transduction mediated by HER kinases (40). In prostate cancer, SRC family kinases and FAK signaling are frequently hyperfunctional and have been associated with poor patient outcome, as well as resistance to antihormonal therapies (41). In addition, previous studies have demonstrated that SRC is involved in resistance to epidermal growth factor receptor inhibitors, which has been associated with poor outcomes in NPC patients treated with lapatinib and cetuximab (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…28 In breast cancer, Src kinases are higher expressed in malignant tissue compared with benign breast samples, 29 and in prostate samples increased Src expression correlates with a shorter time to castration response and poorer survival. 30 Dasatinib, an Src kinase inhibitor, prevented prostate cancer growth in a xenograft model in castrated mice. 31 Moreover, a number of clinical trials have assessed the potential of dasatinib in prostate cancer.…”
Section: Srcmentioning
confidence: 99%